Severity of obstructive sleep apnea is associated with the nocturnal fluctuation of pulse rate, but not with that of blood pressure, in older hypertensive patients receiving calcium channel blockers. Issue 7 (1st May 2019) - Nozato, Satoko; Yamamoto, Koichi; Nozato, Yoichi; Akasaka, Hiroshi; Hongyo, Kazuhiro; Takeda, Masao; Takami, Yoichi; Takeya, Yasushi; Sugimoto, Ken; Ito, Norihisa; Rakugi, Hiromi
Abstract : Aim: Obstructive sleep apnea (OSA) is associated with increased variability in nocturnal blood pressure (BP). Calcium channel blockers (CCB) are superior to other classes of antihypertensives in decreasing BP variability. We investigated whether OSA severity is associated with nocturnal BP variability in older hypertensive patients treated with CCB. Methods: We measured home systolic and diastolic BP and pulse rate (PR) automatically during sleep at an interval of an hour once a week using an electronic sphygmomanometer in 29 hypertensive patients (aged ≥65 years) receiving CCB. We calculated the coefficient of variation (CV) from four consecutive measurements. All patients underwent a home‐based portable sleep study. Results: We found no difference in PR, BP or CV of BP between the patients with no‐to‐mild OSA and with moderate‐to‐severe OSA, categorized by the respiratory disturbance index (RDI) and 3% oxygen desaturation index (ODI). The CV of PR in patients with moderate‐to‐severe OSA was higher than the patients with no‐to‐mild OSA categorized by 3% ODI ( P  = 0.01). Body mass index was correlated with RDI and 3% ODI ( r  = 0.56 and 0.43, respectively). The CV of BP did not correlate to RDI or 3% ODI. The CV of PR was positively correlated both with RDI and with 3% ODI ( r  = 0.41 and 0.42, respectively). Conclusions: The severity of OSA was associated with PR variability, but not with BP variability, in older patients receiving CCB. Our results suggest the need for future studies to determine whether CCB can suppress the influence of OSA on BP fluctuation during sleep.Geriatr Gerontol Int 2019; 19: 604–610 .